A rare non-Robertsonian translocation involving chromosomes 15 and 21 - Baruffi, Marcelo Razera; Souza, Deise Helena; Silva, Rosana Aparecida Bicudo; Ramos, Ester Silveira; Moretti-Ferreira, Danilo (São Paulo Medical Journal, 2013)
CONTEXT: Robertsonian translocations (RT) are among the most common balanced structural rearrangements in humans and comprise complete chromatin fusion of the long arm of two acrocentric chromosomes. Nevertheless, non-Robertsonian translocation involving these chromosomes is a rare event. CASE REPORT: We report a de novo unbalanced translocation involving chromosomes 15 and 21. The newborn was the daughter of a 29-year-old mother and a 42-year-old father. The couple was non-consanguineous. Clinical findings led to the diagnosis of Down syndrome (DS) with severe congenital heart defects (persistent arterial duct, and complete atrioventricular septal defect), as well as low birth length and weight (< 5th and < 10th percentile, respectively, based on specific measurement curves for DS). Conventional cytogenetic analysis revealed the karyotype 46,XX,der(15)(15pter→15q26.2::21q11.2→21qter). The translocation was confirmed by means of fluorescence in situ hybridization. The parents had normal karyotypes. CONCLUSIONS: Differently from RT, in our case a rare event occurred involving the distal segment of 15q and the proximal segment of 21q. Only two reports of this translocation, involving chromosomes 15 and 21 but different breakpoints, have been described so far. The association between 21q duplication and 15q deletion makes it difficult to separate the effect of each chromosome, but might also be responsible for increasing the growth retardation, as detected in our case. Cytogenetic analysis on DS patients is mandatory not only to confirm the diagnosis, but also to assess the risk of recurrence at genetic counseling, as well as to evaluate the contribution of other chromosome aberrations in the final phenotyp.